Skills and competences of adult educators: learning experiences with senior citizens - Patrício, Maria Raquel (2014)
Due to the increasing importance given to lifelong and intergenerational learning, adult educators are taking on new roles and their work is gaining greater impact, especially in a general context of financial and social crisis. Therefore it is important to respond to the educational challenge of an ageing population in Europe and to help in the provision of pathways to improve adults’ knowledge, competences, culture and education. Involving a rich assortment of actors and contexts, adult education has an heterogeneous nature, engaging people, working with adults in exploring issues of intergenerational competence. In addition, such professionals (or volunteers!) ought to identify the competences required for adult education and to find ways in which their performance may be developed. The improvement of these skills and competences will help increasing seniors access and in widening participation and motivation in adult education, thus making the learning experience of adults more relevant, enjoyable and fun. On the one hand, the recognition and feedback given by participants and the experience of working is decisive for the development of specific skills and competences for professionals in the adult learning sector; on the other hand, competence profile of adult educators is complex and involves a multi-dimensional set of skills, personal attitudes and values as well as knowledge and understanding. The need for more information on adult education justifies more action research and action learning in this field. Therefore, the aim of this communication is to present some experiences in adult education, in the context of non-formal and intergenerational learning, focused on various and different aspects of the teaching and learning process and also on how to improve the skills and competences of adult educators in their actual practice. Trying to find a fine answer to the question “What is the importance of learning experience with senior citizens and its contribution for professional development?” we intend to describe, analyse and reflect different training intergenerational contexts in non-formal adult education and identify the factors that influence teacher and learning work that can contribute to professional development. The need for a proper emphasis on diversity and on motivating adults, using different learning methods, styles and techniques assuming the expertise and background of the learners is being taken into suitable consideration.